Odor Modulation by Warming/Cooling Nose Based on Cross-modal Effect - Fujino, Yuichi; Matsukura, Haruka; Iwai, Daisuke; Sato, Kosuke (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
Presentation of odors is considered to be important as a means for giving a sense of presence. However, the basic odors have not been established to generate any kinds of odors by combining them, like the three primary colors in vision, the basic tastes in gustation. In order to present various kinds of odors, in general, it is necessary to prepare each corresponding odorant. In this research, an odor modulation method is proposed based on a cross-modal effect between olfaction and thermal sensation, which might be able to decrease the number of odorants used to generate odors presented to the user. The experimental results are reported to show that sensation of odors can be modulated by presenting warm/cool air with the odors even if the same odors are presented to the subjects.